Resveratrol Prevents Hyperleptinemia and Central Leptin Resistance in Adult Rats Programmed by Early Weaning - Franco, J. G.; Lisboa, P. C.; da Silva Lima, N.; Peixoto-Silva, N.; Maia, L. A.; Oliveira, E.; Passos, M. C. F.; de Moura, E. G. (Hormone and Metabolic Research, 2014)
We have previously shown that early weaning in rats increases the risk of obesity and insulin resistance at adulthood, and leptin resistance can be a prime factor leading to these changes. Resveratrol is reported to decrease oxidative stress, insulin resistance, and cardiovascular risk. However, there is no report about its effect on leptin resistance. Thus, in this study we have evaluated resveratrol-preventing effect on the development of visceral obesity, insulin, and leptin resistance in rats programmed by early weaning. To induce early weaning, lactating dams were separated into 2 groups: early weaning (EW) – dams were wrapped with a bandage to interrupt lactation in the last 3 days of lactation and control (C) – dams whose pups had free access to milk during throughout lactation period (21 days). At 150 days-old, EW offspring were subdivided into 2 groups: EW+res – treated with resveratrol solution (30 mg/kg BW/day) or EW – receiving equal volume of vehicle solution, both given by gavage during 30 days. Control group received vehicle solution. Resveratrol prevented the higher body weight, hyperphagia, visceral obesity, hyperleptinemia, hyperglycemia, insulin resistance, and hypoadiponectinemia at adulthood in animals that were early weaned. Leptin resistance, associated with lower JAK2 and pSTAT3 and higher NPY in hypothalamus of EW rats were also normalized by resveratrol. The present results suggest that resveratrol is useful as therapeutic tool in treating obesity, mainly because it prevents the development of central leptin resistance.
Keywords: metabolic programming; polyphenol; appetite control; visceral adiposity